The Results of the Cluster and Factor Analysis of the Living Standards of the RA Households - Aghabekyan, Edgar; Avagyan, Gayane; Davtyan, Kamo; Saratikyan, Luiza («Տնտեսագետ» հրատ․)
Based on the results of the comprehensive survey of the living standards of households in Armenia, this research aims to identify and evaluate the socio-economic situation of households and the country in general, as well as to provide a more detailed and clear understanding of the state of the population's living standards, intending to improve relevant policies and programs. The research used the SPSS statistical package through cluster and factor analysis. The application of this analytical tool provides an opportunity to identify the main groups that are most vulnerable and, therefore, need more focused and targeted solutions in support programs of both the governmental and other non-governmental stakeholders. Through the latter, it is also possible to better understand the needs of households, regardless of their income level, spending structure, or consumption behavior. The socio-economic conditions of households in Armenia differ greatly according to regions and clusters. Some regions (Yerevan, Kotayk, Syunik) are more prosperous, while the poverty level remains high in the most vulnerable areas (Shirak, Vayots Dzor, Tavush). Regional disparities require targeted policies to strengthen social protection and equalize economic opportunities for different communities.
Keywords: Macroeconomics